Power and the land - Benét, Stephen Vincent, 1898-1943.
Includes prologue and commentary for the film and a set of stills and clips.
Author and poet.
Collection material in English.
Keywords: Power and the land (Motion picture); Motion picture plays, American; Authors; Poets